Xylene removal from contaminated airborne by using activated carbon and potassium permanganate / Ruwaidah Jasmin - Jasmin, Ruwaidah (Faculty of Applied Sciences, 2009)
People spend 80-90% of their time indoors rather than outdoor. Our indoor environment has important effects on human health and work efficiency. In occupational settings, one of the official agencies, Occupational Safety and Health (OSH), under the Use and Standard of Exposure of Chemical Hazardous to Health Regulation 2000 (USECHH) have established an 8-hour time-weighted average permissible exposure limit (TWA PEL) of 100 ppm or 435 mg/m³ for xylene isomers. Levels only slightly above the 8- hour TWA may cause lack of coordination and amnesia. Even levels lower than 50 ppm can cause drowsiness, moderate fatigue and headache. In this study, it focus on the used of activated carbon impregnated with potassium permanganate to remove xylene from the contaminated airborne for human health. It is an adsorption technique, which is one of the indoor air purification for removing indoor air pollutants and improving Indoor Air Quality (IAQ) under the circumstances that the ventilation and the control of pollution sources are impossible. An analytical method, based on separation with gas chromatography (GC) and Flame Ionization Detector (FID) as detector, was used for the separation, detection and quantitation of xylene and the result shows the concentration of xylene is reduced from 110.6 to 18.1 mg/m³ within 300 minutes of sampling inside the mini booth. A further study is suggested on activated carbon and indoor air quality control for healthy indoor air environment.